Impact of entrepreneur’s characteristics on shaping dynamic enterprise capabilities in international operations - Malewska, Kamila; Ratajczak-Mrozek, Milena; Sajdak, Maja (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
More and more companies are undertaking strategic changes and deciding to conduct international activities related to servicing foreign customers, international cooperation or solely obtaining foreign raw materials. This is possible, among other things, thanks to dynamic capabilities that are a response to the growing dynamics of the business environment. Dynamic capabilities exemplify the possibility of reconfiguration and changes in the resources and competences base in order to adapt to highly dynamic environment. It is postulated in the literature that the entrepreneur’s personality characteristics (the so-called entrepreneur’s profile) have an impact on the effectiveness of companies’ strategic actions and are important for their international activities. However, there is a lack of research combining these perspectives, that is combining the entrepreneurial characteristics in the perspective of dynamic capabilities enabling effective international activity. The aim of the article is to identify the impact of entrepreneurial characteristics on the process of shaping the dynamic capabilities of companies enabling these companies’ effective business activities on international markets. The article, based on analysis of the literature of the subject, proposes a conceptual model assuming the existence of links between the entrepreneur’s characteristics, the individual entrepreneurial dynamic capabilities, the company’s dynamic capabilities and the effectiveness of strategic actions on international markets. The model indicates that the entrepreneur’s characteristics translate into the dynamic capabilities of the enterprise, and within them an important role is played by the entrepreneurial cognitive capabilities.